The role of glycemic status in adverse outcomes following ENT surgery - Schaschinger, Thomas; Niederegger, Tobias; Brandt, Jule; Hoch, Cosima C.; Knoedler, Samuel; Matar, Dany Y.; Orgill, Dennis P.; Knoedler, Leonard; Rendenbach, Carsten; Heiland, Max; Klimitz, Felix J.; Hundeshagen, Gabriel; et al. (The laryngoscope, 2026)
Objectives Poor glycemic control is a known risk factor for adverse surgical outcomes, yet its impact in otolaryngologic (ENT) procedures remains underexplored. This study investigates the association between preoperative hemoglobin A1c (HbA1c) levels and postoperative outcomes in ENT surgical patients, while also assessing the prevalence of unrecognized dysglycemia. Methods ENT patients within the ACS-NSQIP database (2021-2023) were stratified into glycemic groups based on diabetes diagnosis and HbA1c thresholds. Multivariable logistic regression assessed the independent association of HbA1c and composite outcomes, which included any-, surgical-, and medical complications, readmission, and reoperation. Results Among 14,034 ENT patients, 6.2% had HbA1c values indicative of undiagnosed diabetes. Complication rates increased with worsening glycemic control, a persisting trend across many procedures. Multivariate analysis revealed that patients with a diabetes diagnosis and poor glycemic control experienced higher odds of any- (OR 1.4, 95% CI 1.2-1.8, p = 0.001), surgical- (OR 1.4, 95% CI 1.1-2.0, p = 0.02), and medical complications (OR 1.9, 95% CI 1.3-2.7, p < 0.001), as well as hospital readmissions (OR 1.5, 95% CI 1.0-2.1, p = 0.04), while those with undiagnosed pre-diabetes demonstrated lower odds of medical complications (OR 0.66, 95% CI 0.45-0.96, p = 0.03) when compared to healthy individuals. Conclusion Glycemic status is a strong predictor of short-term postoperative complications in ENT surgery. Importantly, a substantial portion of patients had undiagnosed diabetes or prediabetes, emphasizing the need for preoperative HbA1c screening to identify at-risk individuals and enable early intervention. Level of Evidence 3.
Zuerst veröffentlicht: 09. Dezember 2025
Gesehen am 27.02.2026